PEMETAAN PROBLEMATIKA KOMUNIKASI DALAM AKTIVITAS DAKWAH DI MAJLIS TAKLIM KOTA PEKANBARU - Ginda Ginda; Yefni Yefni (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
This study is intended to find problems of communication in missionary activities in taklim. Da'wah is an activity that can not be separated from communication activities. Even the missionary activities in the broadest sense is the communication itself. From the perspective of science